Footprint of a new formation in the conservation of the heritage forged in University of Piura - Coahila Osorio, Alberto (2021)
This article will examine the panorama of teaching the Heritage Conservation subject at the University of Piura (UDEP). We will present a compilation and analysis of the evolution, methodology, and results of the subject over time through experiences of the student’s work and testimonies who have taken the subject in different periods.  The purpose is to increase interest in the implementation and reinforcement of related courses in university, which do not limit the exploration of students, and encourage a future job in the conservation of heritage in Peru.